Muscle-sparing posterolateral thoracotomy for esophageal atresia Vogt Type 3b - Rahul Gupta (EL-Med-Pub, 2022)
Background: Posterolateral muscle cutting thoracotomy is the gold standard approach to repair esophageal atresia with distal tracheoesophageal fistula. This technique is associated with morbidities in terms of poor motor and aesthetic outcomes. We aim to share our experience with muscle-sparing skin crease incision posterolateral thoracotomy for esophageal atresia Vogt type 3b. Methods: It was a retrospective observational study conducted over a period of 3 years and 6 months from January 2016 to June 2019 at two tertiary care teaching institutes. All patients with esophageal atresia having distal tracheoesophageal fistula were included. Results: Fifty-nine neonates underwent muscle-sparing thoracotomy, with 23 males and 36 females. The 34 (58%) neonates had low birth weight. Anorectal malformation (ARM) was the most common (6) associated major malformation(18). Intraoperative findings included long gap EA (6), right aortic arch (RAA, 3), aberrant vessels (1), and long upper pouch (1). Conversion to muscle cutting approach (during early learning curve) was performed in 8 cases i.e. long gap EA (3), RAA (2), Subglottic stenosis (2), others (1). No intraoperative complication was encountered; postoperative seroma formation (related to the approach) was observed in 2 (3.4%) neonates. Most of the patients achieved satisfactory functional and aesthetic outcomes. Conclusions: Muscle-sparing skin crease incision posterolateral thoracotomy is a viable approach for repair of esophageal atresia with distal tracheoesophageal fistula. The technique is easy to perform with adequate exposure and provides satisfactory functional and aesthetic outcomes with relatively minimum morbidity.